Transcriptome profiling in Parkinson's leukocytes: from early diagnostics to neuroimmune therapeutic prospects. (February 2016) - Simchovitz, Alon; Soreq, Lilach; Soreq, Hermona
Highlights: Currently late Parkinson's disease diagnosis only allows palliative treatment. Studies in patients and animal models implicate neuroimmune malfunctioning. RNA-sequencing and microarray analyses indicate RNA-mediated neuroimmune errors. New technologies may identify peripheral neuroimmune-related disease biomarkers. Interference with neuroimmune mediators may enable curative treatment. Abstract : Parkinson's disease (PD) involves motor symptoms reflecting the progressive degeneration of dopaminergic neurons in the substantia nigra. However, diagnosis is only enabled late in the disease, limiting treatment to palliative assistance. Here, we review recently generated transcriptional profiling datasets from blood and brain RNA of human PD cohorts and animal models that may offer unprecedented progress in PD research. Specifically, advanced analysis techniques demonstrated functionally inter-related underlying impairments of RNA metabolism and neuroimmune signalling processes. Identifying novel biomarkers in serum and nucleated blood cells, including protein networks and non-coding RNAs can drive discovery of the molecular mechanisms involved and reveal new targets for therapeutic intervention, posing a dual diagnosis/treatment opportunity for limiting the exacerbation of neuroinflammatory events in PD.